Improving Early Childhood Development through Community Mobilization and Integrated Planning for Children : Results from the Evaluation of Bachpan Program, Ratlam District, Madhya Pradesh, India - Sankar, Deepa (World Bank, Washington, DC, 2013)
This study reports the results of an impact evaluation of a pilot project implemented in 220 villages in Bajna block, Ratlam district, Madhya Pradesh (MP), India. The 30-month pilot was designed to improve early childhood development outcomes through: (a) creating awareness on child development issues among households and the community; (b) strengthening linkages between different service providers; (c) intensifying the connection between the community, panchayat (local governments), and service providers; (d) facilitating the formation of Village Resource Groups (VRGs) with representatives of the community, panchayat, and service providers to ensure better convergence and coordination of service delivery; (e) developing integrated village-level action plans around the needs of the child; and (f) advocating and lobbying with local, district, and state administration for flexible allocation of resources. The evaluation assessed the impact of the project on health, education, and nutrition milestones or outcomes or outputs identified for each stage of child development. This report is structured as follows: chapter one gives background; chapter two presents evaluation of the results of the pilot project; chapter three presents progress in processes and identified outcomes or milestones; and chapter four deals with Bachpan-lessons learned.